Sustainable Bicycle Path Planning for Medium-Sized Cities by Using GIS-Based Multicriteria Decision-Making Analysis: A Case Study From Turkey - Olgun, Rifat (Fırat University, 2020)
The world's population is increasing rapidly and consequently, urban areas are also expanding and developing rapidly. This growth and development in cities leads to the differentiation of urban transportation systems and, in particular, the increase in the number of motor vehicles. This increase in the number of motor vehicles in order to provide transportation leads to many problems. In order to prevent these problems, many researchers and decision makers state that sustainable transportation systems such as public transportation, walking and cycling should be used. The objective of the research is to develop a sustainable bike path proposal for cities through GIS-based multicriteria decision-making analysis, taking into account physical, environmental and visual factors of medium-sized cities. In this context, the physical, environmental and visual factors of the city of Nigde, Turkey, which is considered to be a medium-sized city, were evaluated with GIS-based multicriteria decision-making analysis, and a sustainable bike path proposal was developed for Nigde according to the zoning plans.